Experimental Methodology to Determine Thermal Conductivity of Nanofluids by Using a Commercial Transient Hot-Wire Device - Jose I. Prado; Uxía Calviño; Luis Lugo (Applied Sciences, 2021)
The lack of a standard experimental procedure to determine thermal conductivity of fluids is noticeable in heat transfer processes from practical and fundamental perspectives. Since a wide variety of techniques have been used, reported literature data have huge discrepancies. A common practice is using manufactured thermal conductivity meters for nanofluids, which can standardize the measurements but are also somewhat inaccurate. In this study, a new methodology to perform reliable measurements with a recent commercial transient hot-wire device is introduced. Accordingly, some extensively studied fluids in the literature (water, ethylene glycol, ethylene glycol:water mixture 50:50 vol%, propylene glycol, and n-tetradecane) covering the range 0.100 to 0.700 W m−1 K−1 were used to check the device in the temperature range 283.15 to 333.15 K. Deviations between the collected data and the theoretical model, and repeatabilities and deviations between reported and literature values, were analyzed. Systematic deviations in raw data were found, and a correction factor depending on the mean thermal conductivity was proposed to operate with nanofluids. Considering all tested effects, the expanded (k = 2) uncertainty of the device was set as 5%. This proposed methodology was also checked with n-hexadecane and magnesium-oxide-based n-tetradecane nanofluids.